Hukum Menyalatkan Jenazah Pendukung Penista Agama dan Pemilih Non-Muslim menjadi Pemimpin - Mahmuddin, Ronny (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2017)
Refusing to perform prayer for the dead who supported blasphemy and voted for an infidel to be a ruler for a Muslim society implies the accusation of someone to be an unbeliever.Labelling a Muslim to be an unbeliever is equal to accusing him to commit apostasy, which subsequently means that it is permissable either to take his life or to shed his blood, even to divorce him from his wife. When he dies, his body will not be: performed for ablution, wrapped by shroud, held for prayer, burried in Muslim burial area, and his wealth is not allowed to be inherited by any of his inheritees. Moreover, he is to fall into the Hellfire eternally for dying upon infidel state. This paper was going to scrutinize the issue of